NIAT UNTUK MENGAMBIL CHARTERED ACCOUNTANT DENGAN THEORY OF PLANNED BEHAVIOR - Wardani, Guhti Ayu Sri; Januarti, Indira (JURNAL AKUNTANSI DAN AUDITING, 2015)
This study aims to analyze and provide empirical evidence about the influence of perceptions and attitudes, subjective norms, and perceived behavioral control on the intention of students to take a chartered accountant. The sample in this study is undergraduate’s students in Faculty of Economics Department of Accounting 2015 and PPAk’s students class of 2014 and 2015 at Diponegoro University were 107 respondents. The method of collecting data is a survey method by distributing questionnaire to respondents either directly or electronically. The data was analyzed using logistics regression analysis. The results showed subjective norm has a significant influence on the intention of student to take a Chartered Accountant. While factors perceptions and attitudes and perceived behavioral control have no a significant influence on the intention of students to take Charetered Accountant.